The Production and Carbon Emission Efficiency Analysis of the Manufacturing Sector across Six Provinces in Java: An SBM Approach (2018–2022) - Nadillah Lilhidayah; Deni Kusumawardani (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Objective: This study aims to estimate green efficiency levels in the manufacturing sector across six provinces on Java Island and to identify benchmarks for environmentally friendly industrial governance policies, both spatially and temporally. Methods: A quantitative-descriptive approach was employed, utilizing input-oriented Slack-Based Measure Data Envelopment Analysis (SBM-DEA) modeling under the assumption of Variable Returns to Scale (VRS). The geographical scope covers six provinces on Java Island (Banten, DKI Jakarta, West Java, Central Java, DI Yogyakarta, and East Java) over the 2018–2022 observation period. Input variables include capital, labor, and fossil energy consumption, while output variables consist of industrial GDP (desirable output) and carbon dioxide (CO2) emissions as a negative environmental residual effect (undesirable output). Data were gathered from secondary reports by Statistics Indonesia (BPS) and the Ministry of Energy and Mineral Resources (ESDM). Results: The findings reveal a stark dichotomy in efficiency performance. Banten, DKI Jakarta, West Java, and DI Yogyakarta consistently maintained perfect efficiency status (a score of 1.0000) throughout the observation period. Conversely, Central Java (average 0.8556) and East Java (average 0.7034) experienced persistent green inefficiency due to excessive emissions (slacks) and energy input wastage. Benchmark analysis (Lambda) revealed dynamic shifts: Central Java was self-efficient during the pandemic but saw a decline post-pandemic in 2022, whereas East Java’s reference point for improvement shifted entirely from DI Yogyakarta (2018) toward the low-carbon technology characteristics of DKI Jakarta and West Java (2020–2022), with contribution weights exceeding 60%. Implications: The findings highlight the need for regional authorities in Central and East Java to move away from "business-as-usual" policies. Concrete policy interventions are recommended, including the implementation of mandatory energy audits for the heavy industry sector, the provision of green fiscal incentives, and the standardization of integrated industrial zones (eco-industrial parks) modeled after the West Java clusters. Future studies should expand the scope of analysis by utilizing firm-level data and incorporating other environmental pollutants, such as liquid waste and SOx/NOx emissions.